The Aquifer-CO2Leak project: Numerical modeling for the design of a CO2 injection experiment in the saturated zone of the Saint-Emilion (France) site. (January 2021) - Gassara, O.; Estublier, A.; Garcia, B.; Noirez, S.; Cerepi, A.; Loisy, C.; Le Roux, O.; Petit, A.; Rossi, L.; Kennedy, S.; Brichart, T.; Chiquet, P.; et al.
Highlights: Carbon dioxide CO2 migration in carbonated aquifers within the context of Carbon Capture and Storage (CCS): pre-modelling of a CO2 injection experiment in Saint Emilion, France. Fluid flow model to simulate the migration of the following injected dissolved species: CO2, krypton, fluorescent molecule. Sensitivity analysis of the uncertain model parameters in order to assess the working assumptions: assessment of the species concentration uncertainty. Abstract: The objective of the Aquifer-CO2 Leak project is to get insights into carbon dioxide CO2 migration in aquifers within the context of Carbon Capture and Storage (CCS) and to test the different equipment necessary for CO2 monitoring. The underlying idea is to develop an experiment in the saturated zone (phreatic) of the underground limestone quarry located at Gironde department (France). It consists in injecting water, carrying dissolved gases (CO2 and krypton) and a fluorescent molecule, under controlled conditions. In this paper, we present the dimensioning study of the experiment by numerical simulations carried out using the simulator CooresFlow (IFPEN's in-house simulator for reactive transport in porous media). The important experiment parameters (injection flow rate, injected volume, the time to return in system equilibrium and wells location) were successfully estimated. In particular, the variation of species concentration in time and space was simulated and analyzed to define an experimental measurement schedule for the planned survey. Finally, a sensitivity analysis of the uncertain model parameters is presented. We found that the water table level and the dispersivity of the porous medium appear to be the most "sensitive" parameters.